FRI0441 Risk factors of chloroquine maculopathy and role of plasma chloroquine and desethylchloroquine concentrations in predicting chloroquine maculopathy. (23rd January 2014) - Chiowchanwisawakit, P.; Nilganuwong, S.; Srinonprasert, V.; Boonprasert, R.; Chandranipapongse, W.; Chatsiricharoenkul, S.; Katchamart, W.; Pongnarin, P.; Koolvisoot, A.; Arromdee, E.; Ruangvaravate, N.
Abstract : Objectives: To investigate the risk factors for chloroquine maculopathy (CM), and to explore factors associated with plasma chloroquine (CQ) and desethylchloroquine (DCQ) levels. Methods: Two-hundred and thirty-three rheumatoid arthritis (RA) patients who had taken CQ at least 6 months with stable CQ dosage for at least 2 months were included between March 1, 2010 and September 30, 2011 at Siriraj Hospital, Thailand. CM was diagnosed by ophthalmologist utilizing dilated ocular examination and Humphrey visual field 10-2 white protocol. Plasma CQ and DCQ levels were determined by liquid chromatography tandem mass spectrometry method. Logistic regression models were applied to explore risk factors associated with CM. Results: One hundred and ninety-three patients were included with median CQ duration (range) of 50.2 (6.0 – 269.8) months and cumulative dose of 137.4 (16.4-1226.5) gm. The prevalence of CM was 13.5%. One hundred and fifty seven plasma samples were available for determining the CQ and DCQ levels. Factors associated with developing CM identified from univariate analysis were age more than 60 years old, and poor creatinine clearance (CCl) with odds ratio (OR) (95%CI) of 5.79 (2.42, 13.84), and 0.98 (0.96, 1.00), respectively while current daily CQ dose from 2.5 mg/kg had marginal association, p=0.06. Plasma CQ and DCQ was not associated with CM with OR of 1.00 (1.00, 1.01) and 0.99 (0.98, 1.01), respectively. In multivariate analysis, older age, CQ exposure duration >5 years, and current daily dose of at least 2.5 mg/kg-IBW were the factors significantly associated with CM with OR of 5.89 (2.38, 14.57), 2.94 (1.10, 7.83), and 3.32 (1.04, 10.60), respectively while plasma CQ and DCQ showed no association with CM. With respect to plasma CQ and DCQ levels, current daily CQ dosage had the strongest positive correlation with both plasma levels as shown in the table . Conclusions: Age more than 60 year-old, duration of CQ use more than 5 years and current CQ dose ≥2.5 mg/kg-IBW/day were the risk factors of CM. The plasma CQ or DCQ levels demonstrated no correlation in developing CM. The plasma levels were strongly associated with current daily dose of CQ. Funding: Siriraj Research Development Fund, Faculty of Medicine Siriraj Hospital, Mahidol University. Disclosure of Interest: None Declared